Application of modern warehouse technology in the Slovenian automotive industry - Škerlič, Sebastjan; Muha, Robert; Sokolovskij, Edgar (Transport, 2017)
The objective of this paper is to demonstrate the usefulness and reliability of modern warehouse technology for suppliers in the automotive industry and to identify the potential causes preventing it from being used more in practice. In recent years, we have seen great progress made in the development of modern warehouse solutions, as well as a dramatic rise in research on the issues related to the introduction of modern technology and interaction between operators and automation. However, a look at some of the existing studies on the usefulness of the use of modern technology reveals that their conclusions are often contradictory. The results of statistical analysis of Slovenian companies that operate as suppliers in the international automotive industry show that modern warehousing technology is reliable and safe to use, but more than 60% of companies fail to take advantage of its benefits. These companies are also using basic warehouse technology, despite the fact that such technology does not ensure a sense of safety in the warehouse. In the medium term, this could put them at a disadvantage against competitors in the demanding sector of the automotive industry. The results of the study provide additional starting points for understanding human use of modern warehouse technology, which can lead to improvements in how warehouse systems are designed, more effective employee training methods and a reasonable and balanced policy for the automation of the warehousing processes.